Theorem on the union of two topologically flat cells of codimension 1 in ℝ n (Abstract and Applied Analysis)
In this paper we give a complete and improved proof of the "Theorem on the union of two ( n−1 ) -cells." First time it was proved by the author in the form of reduction to the earlier author's technique. Then the same reduction by the same method was carried out by Kirby. The proof presented here gives a more clear reduction. We also present here the exposition of this technique in application to the given task. Besides, we use a modification of the method, connected with cyclic ramified coverings, that allows us to bypass referring to the engulfing lemma as well as to other multidimensional results, and so the theorem is proved also for spaces of any dimension. Thus, our exposition is complete and does not require references to other works for the needed technique.